(untitled) (Historia, 2021)
This edited volume aims to investigate a theme that has received little analytical attention in the emerging body of literature on witchcraft in Africa, namely whether contemplations about witchcraft can contribute towards understanding processes of warfare and peace-building. Nicolini claims that witchcraft and magic has played an important historical role in political and military conflicts. She observes that anti-colonial resistance movements have invoked the supernatural in political mobilisation, rituals of healing have been deployed in post-colonial situations, and that witchcraft and magic have been invoked in numerous power struggles in the continent through time.